(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The article is devoted to the problem of creating conditions for the application of lean technologies in the university of arts and culture, the need to create prerequisites in a higher educational institution for the preparation of favorable soil, which will allow the effective use of lean technologies. The importance of using lean technologies as an innovative way of developing higher education is considered. The authors reflect on a rethinking of approaches to educational activity, the use of design methods and lean manufacturing in relation to the processes of a creative university. The methods of analysis and synthesis were used in the work, the key, in the opinion of the authors, conditions necessary for the formation and development of the concept of lean manufacturing in a higher educational institution were determined, supported by examples of projects implemented on the basis of the Belgorod State Institute of Arts and Culture.